PENGARUH DIGITALISASI, PEMBIAYAAN DAN MANAJEMEN KEUANGAN TERHADAP PERTUMBUHAN UMKM DI ACEH - Saiful Bahgia; Rahmaniar; Lisnawati (JURNAL KREASI RAKYAT, 2025)
This study aims to explore and analyze the influence of digitalization, financing, and financial management on the growth of MSMEs in Aceh. The research method uses a quantitative descriptive approach and conducts classical assumption tests and multiple linear regression tests. Data were obtained directly through distributing questionnaires to 70 respondents. The results of the study indicate that, simultaneously, digitalization, financing, and financial management influence the growth rate of MSMEs in Aceh. The independent variables (X) together have a contribution of 36.7% in explaining the growth rate of MSMEs in Aceh. While the remaining 63.3% is influenced by other variables not explained in this study. Partially, the digitalization variable (X1) of 0.277 and financing (X2) of 0.537 have a significant effect on the growth rate of MSMEs. Meanwhile, the financial management variable (X3) does not have a significant effect on the growth of MSMEs in Aceh. This study recommends further studies specifically examining the problems that hinder the growth of MSMEs. The government's presence is needed to maintain the significance of the growth and sustainability of MSMEs in Aceh.